Integrating Poor Countries into the World Trading System. (Economic Issues; Economic Issues ;, 2006)
Efforts to liberalize world trade are increasingly focusing on strengthening the links between low-income countries' trade policies and their development strategies. However, although greater trade openness promises faster growth for poor countries, it also presents risks to those with small and undiversified economies. This pamphlet explores research by Fund staff into the nature and magnitude of these risks and proposes targeted policy solutions to ease adjustments and encourage developing countries to choose fuller participation in the world trading system.